Educational systems and gender segregation in education : a three-country comparison of Germany, Norway and Canada - Imdorf, Christian [Verfasser]; Hegna, Kristinn [Verfasser]; Eberhard, Verena [Verfasser]; Doray, Pierre [Verfasser] (My University, 2015)
"How do institutional settings and their embedded policy principles affect gender-typed enrolment in educational programmes? Based on gender-sensitive theories on career choice, we hypothesised that gender segregation in education is higher with a wider range of offers of vocational programmes. By analysing youth survey and panel data, we tested this assumption for Germany, Norway and Canada, three countries whose educational systems represent a different mix of academic, vocational and universalistic education principles. We found that vocational programmes are considerably more gender-segregated than are academic (e.g. university) programmes. Men, more so than women, can avoid gender-typed programmes by passing on to a university education. This in turn means that as long as their secondary school achievement does not allow for a higher education career, they have a higher likelihood of being allocated to male-typed programmes in the vocational education and training (VET) system. In addition, social background and the age at which students have to choose educational offers impact on the transition to gendered educational programmes. Overall, gender segregation in education is highest in Germany and the lowest in Canada. We interpret the differences between these countries with respect to the constellations of educational principles and policies in the respective countries." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; G 2.4.5 Gender Mainstreaming; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; Berufsbildungssystem; Berufsbildungspolitik; Einflussfaktor; Geschlechtersegregation; Internationaler Vergleich; Bundesrepublik Deutschland; Norwegen; Kanada